Viscosity, heat conductivity, and Prandtl number effects in the Rayleigh-Taylor Instability - Chen, Feng; Xu, Ai-Guo; Zhang, Guang-Cai (Frontiers of physics, 2016)
The two-dimensional Rayleigh-Taylor instability problem is simulated with a multiple-relaxation-timediscrete Boltzmann model with a gravity term. Viscosity, heat conductivity, and Prandtl number ef-fects are probed from macroscopic and nonequilibrium viewpoints. In the macro sense, both viscosityand heat conduction show a significant inhibitory effect in the reacceleration stage, which is mainlyachieved by inhibiting the development of the Kelvin-Helmholtz instability. Before this, the Prandtlnumber effect is not sensitive. Viscosity, heat conductivity, and Prandtl number effects on nonequilib-rium manifestations and the degree of correlation between the nonuniformity and the nonequilibriumstrength in the complex flow are systematically investigated.